Freestanding high-aspect-ratio gold masks for low-energy, phase-based x-ray microscopy. (22nd January 2023) - Makarova, Olga V; Divan, Ralu; Moldovan, Nicolaie; Czaplewski, David A; Esposito, Michela; Endrizzi, Marco; Tang, Cha-Mei; Ferrara, Joseph D; Olivo, Alessandro
Abstract: High-resolution, x-ray phase contrast microscopy, a key technique with promising potential in biomedical imaging and diagnostics, is based on narrow-slit high-aspect-ratio gold gratings. We present the development, fabrication details, and experimental testing of the freestanding 10 μ m thick gold membrane masks with an array of 0.9–1.5 μ m void slit apertures for a novel low-energy x-ray microscope. The overall mask size is 4 mm × 4 mm, with a grating pitch of 7.5 μ m, 6.0–6.6 μ m wide gold bars are supported by 3 μ m wide crosslinks at 400 μ m intervals. The fabrication process is based on gold electroplating into a silicon mold coated with various thin films to form a voltage barrier, plating base, and sacrificial layer, followed by the mold removal to obtain the freestanding gold membrane with void slit apertures. We discuss key aspects for the materials and processes, including gold structures homogeneity, residual stresses, and prevention of collapsing of the grid elements. We further demonstrate the possibility to obtain high-resolution, high contrast 2D images of biological samples using an incoherent, rotating anode x-ray tube.